Development Results of Integrated Disabilities Care by Using Disabled Persons Database CUP, Sirindhorn Hospital, Khon Kaen Province - ภาวะดี เรณู (Journal of Health Science of Thailand, 2020)
The objective of this study was to develop a set of functioning database of persons with disabilities (PWDs) in the community based on community-based rehabilitation principle in order to formulate and initiate rehabilitation plans and develop the care system for PWDs in the CBR network led by the Sirindhorn Khon Kaen Hospital. The author applied the participatory action research (PAR) method, beginning from briefing community leaders and those responsible for working with PWDs, organizing the training course on PWDs evaluation based on International Classification of Functioning, Disability and Health (ICF) to analyze data and initiate holistic care plans for PWDs and the training course to caregiver, families and communities on caring for PWDs with total dependency. In addition, the method involved adjusting the facilities and encouraging PWDs to get access to educational and vocational rights as well as establishing a PWDs service prototypical center in each district to promote integrated coordination among community care teams to ensure the flow of operation. Implementation results: 2,369 persons were registered as PWDs, and 112 persons were totally dependent while 439 persons had some difficulties and needed assistances. The proportion of PWDs with walking difficulties was 44.93%, followed by 35.79% with memory loss, 34.64% with vision difficulties, and 37.56% with difficulties in getting up from floor. Moreover, 213 persons needed mobility assistive devices, 97 needed home environmental modifications, 14 needed prostheses, and 119 needed employments. CBR-based service plans included home visits and full healthcare services from family care teams, and supply of mobility devices and prostheses from the rehabilitation team at Sirindhorn Khon Kaen Hospital. After initiating the plans and the rehabilitation services with the network, it was discovered that 65 PWDs had been employed while 11 PWDs’ homes received modifications with the financial support from local administrative organizations, and 8 PWDs community services centers were established. Conclusion: the database of functioning status and PWDs’ needs are crucial for formulating PWDs rehabilitation plans. The database could be applied to initiate rehabilitation plans with involved organizations to ensure the delivery of full services to PWDs based on CBR, thus providing effective holistic care plans to help and care for PWDs in the community.